Pengaruh Project Based Learning Terhadap Keterampilan Menulis Laporan Hasil Observasi - Wahid Romadhon; Erato Dido Evandra; R Ratnuswantoro (Universitas PGRI Madiun, 2020)
One reason for the low ability to write observational reports is the method that is often used by teachers in learning Indonesian is only limited to lecture methods, and group work. So the perception that Indonesian is a boring subject because of the lack of learning media used by teachers. This can result in students being less able to work on the results of observational reports. One effort to overcome this is to use an innovative learning model that is the Project based learning model. The purpose of this study, among others, is to determine the effect of project based learning learning models on the skills of writing observational report texts in class X students of Parlaungan Islamic High School in Sidoarjo. The population in this study were grade X students of Parlaungan Waru Sidoarjo Islamic High School as many as 44 students. A total of 22 students as the Experiment class who used the project based learning model and 22 students as the control class who used the direct learning model. After analyzing SPSS 16 using an independent sample test, the probability value = 0.001 < significance level = 5% means that there is an influence of PBL learning models on the skills of writing observational reports